2014
DOI: 10.1002/jor.22667
|View full text |Cite
|
Sign up to set email alerts
|

3D statistical modeling techniques to investigate the anatomy of the sacrum, its bone mass distribution, and the trans‐sacral corridors

Abstract: The complex anatomy of the sacrum makes surgical fracture fixation challenging. We developed statistical models to investigate sacral anatomy with special regard to trans-sacral implant fixation. We used computed tomographies of 20 intact adult pelves to establish 3D statistical models: a surface model of the sacrum and the trans-sacral corridor S1, including principal component analysis (PCA), and an averaged gray value model of the sacrum given in Hounsfield Units. PCA demonstrated large variability in sacra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 33 publications
3
61
0
3
Order By: Relevance
“…Furthermore, the larger range of maximum corridor diameters for S1 compared with the smaller more-sigmoidal distribution for S2 (Fig. 4) shows the greater variability of the S1 osseous corridor shape and confirms the results of Wagner et al [39] based on their investigation of 20 healthy pelves.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, the larger range of maximum corridor diameters for S1 compared with the smaller more-sigmoidal distribution for S2 (Fig. 4) shows the greater variability of the S1 osseous corridor shape and confirms the results of Wagner et al [39] based on their investigation of 20 healthy pelves.…”
Section: Discussionsupporting
confidence: 86%
“…Compared with the oblique sacroiliac screw fixation described by Matta and Saucedo [20], additional fracture pattern like central sacral fractures (Denis Zone III) and bilateral posterior pelvic lesions can be addressed through a unilateral approach, whereas alternative sacroiliac screw fixation from both sides was accompanied with an increased risk of screw misplacement [9,12]. Furthermore, in biomechanical studies, increased fixation strength for transsacral screw placement was reported owing to the screw placement in three additional cortices on the contralateral side instead of placing the screw tip in the weaker cancellous bone of the sacral ala and S1 vertebral body [18,33,39]. This seems particularly important in the increasing number of insufficiency fractures of the pelvic ring caused by osteoporotic bone quality [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, pathways have been recognised to be influenced by sacral anatomy [9]. Thus, the objective of the presented study was to (1) describe the dimensions of the pathway for potential cannulated screw fixation, ensuring secure and optimal fixation of the iliosacral joint (e.g.…”
Section: Introductionmentioning
confidence: 99%